NEEDS AND INTERESTS IN THE FIELD OF SPORTS AMONG STUDENTS IN PEDAGOGICAL SPECIALTIES (TRAKIA JOURNAL OF SCIENCES, 2025)
The present study aims to analyze the needs and interests of students enrolled in pedagogical specialties regarding sports and motor activity, as well as to identify the main factors influencing student initiative.Through the applied research methods, a content analysis of scientific publications was conducted, alongside a survey among students from the Faculty of Education at Trakia University. The results are categorized into the following key areas: the significance of sport for social integration and the development of moral values; the relationship between motor activity and psychosocial well-being; the impact of physical activity on students’ adaptation to the university environment; and differences in students' sports interests according to gender and social background.The analysis of the survey data and theoretical overview highlights the need for a personalized and adaptive approach within university settings to foster student engagement in sports activities. This approach aims to promote physical activity, social inclusion, emotional resilience, and academic success.